Personalized lead exposure information and preventive behaviors in Ivory Coast: Insights from a pilot study - Véronique Gille; Flore Gubert; Camille Saint-Macary; Stéphanie Dos Santos; Franck Houffoué; Hugues Kouadio; Epiphane Marahoua; Petanki Soro; Alexander van Geen (PLoS ONE, 2025)
Lead (Pb) exposure is a major global health concern, particularly for young children, yet awareness of the risks is low. Pb-based paint remains a significant source of exposure in many low- and middle-income countries, despite existing regulations. We investigate whether personalized information on lead in paint can increase awareness and encourage preventive behaviors. As part of a pilot study in Abidjan, Ivory Coast, painted surfaces in pregnant women’s homes were tested using a low-cost Pb detection kit, followed by confirmatory testing with an X-ray fluorescence (XRF) device. Among the final sample of 153 women, those living in homes that tested positive for Pb were 33-35 percentage points more likely to acknowledge their exposure risk. This increased awareness led to self-reported behavioral changes among mothers of young children, including a higher likelihood of preventing children from ingesting paint chips and washing their hands more frequently. We find no impact on self-reported home-cleaning or renovation behaviors. Our findings highlight the potential of personalized information to drive behavioral change in environmental health.